Does When You Die Depend on Where You Live? Evidence from Hurricane Katrina - Deryugina, Tatyana; Molitor, David (American Economic Review, 2020)
We follow Medicare cohorts to estimate Hurricane Katrina's long-run mortality effects on victims initially living in New Orleans. Including the initial shock, the hurricane improved eight-year survival by 2.07 percentage points. Migration to lower-mortality regions explains most of this survival increase. Those migrating to low-versus high-mortality regions look similar at baseline, but their subsequent mortality is 0.83-1.01 percentage points lower per percentage point reduction in local mortality, quantifying causal effects of place on mortality among this population. Migrants' mortality is also lower in destinations with healthier behaviors and higher incomes but is unrelated to local medical spending and quality.